Prior Notification Process Under Merger Regulation: A Comparative Perspective between Vietnam and Several Countries - Hieu, Truong (VNU Journal of Science: Legal Studies; Vol 38 No 2DO - 10.25073/2588-1167/vnuls.4311, 2022)
A prior notification process significantly contributes to the ex-ante merger review. Being familiar with many legal systems, Vietnam has led to the compulsory notification process since the first version of competition law. The Vietnamese Competition Law 2018 still keeps this legal mechanism and also sets up the new notification requirements, which help the merger review process to be more effective. Therefore, other countries’ experience is  helpful for the ongoing Vietnamese progress on merger regulation improvements. In particular, the article suggests that the stage of early consultation that has been popular in Japan and the EU can be lessons for Vietnam.